Alternative approaches to cost sharing for water service to agriculture in Egypt - Perry, C.J. (International Irrigation Management Institute, 1996)
Combines and interprets results from a number of studies that were designed to help the Egyptian government formulate a rational approach to sharing the costs of water services among the beneficiaries-agriculture and other users-and government. Highlights lessons transferable to other countries.